Characterization of CBD deposited CuInSe2 thin film. (February 2018) - Chauhan, Sanjaysinh M.; Chaki, Sunil H.; Deshpande, M.P.; Tailor, Jiten P.; Khimani, Ankurkumar J.
Abstract: Ternary CuInSe2 chalcopyrite semiconductor thin films have been deposited on glass slide substrates by chemical bath deposition technique. The chemical composition of the as-deposited thin film by energy dispersive analysis of X-ray technique showed the film to be near stoichiometric. The X-ray diffraction analysis of the thin film confirmed the tetragonal unit cell structure. All the obtained lattice parameters were in good agreement with the reported data. The crystallite size determined by Scherrer's formula and Hall-Williamsons relation using X-ray diffraction data were in good agreement with each other. The microtopograph study of the as-deposited thin film surfaces by optical and scanning electron microscopy showed that the thin film uniformly covers the entire substrate surface. The atomic force microscopy of the thin film surface showed grains and coalescence between them. The as-deposited thin film possesses direct optical bandgap having value of 1.39 eV being analyzed by Ultra violet-Visible-Near infra red spectroscopy. The optical parameters like reflectance R, transmittance T variation with wavelength and extinction coefficient k, dielectric constant εc and refractive index η variation with incident photons hν showed the as-deposited thin film can be used as an absorber in the visible region of spectrum. The electrical transport properties study confirmed the semiconducting and p-type nature of the as-deposited thin film. The obtained results are comprehensively discussed in this paper.